This book is banned - Haldar, Raj; Patton, Julia (Naperville, Illinois Sourcebooks eXplore, an imprint of Sourcebooks Kids, 2023)
This is a book about dinosaurs. No it's not. Dinosaurs are not allowed. Oh. This is now a book about avocados! Sorry. We deleted those too. FINE. This book is about--nope! Forbidden! Maybe you shouldn't even try reading this book...But what could possibly be inside?Discover just what can happen when ideas are erased instead of expressed.
112297
Keywords: Vocabulary -- Juvenile fiction; Books and reading -- Juvenile fiction; Challenged books -- Juvenile fiction; Prohibited books -- Juvenile fiction; Libraries -- Censorship -- Juvenile fiction; Censorship -- Juvenile fiction; Vocabulary -- Fiction; Juvenile Fiction -- Humorous Stories; Picture books